Pengaruh Penyuluhan Tentang Anemia Dengan Media Animasi Terhadap Pengetahuan Dan Sikap Siswi Di SMP Negeri 1 Lubuk Pakam - Helen Yuniar Sihombing; Abdul Hairuddin Angkat; Sudana Fatahillah Pasaribu; Wanda Lestari (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Anemia is a condition where the number of red blood cells or hemoglobin is less than normal or is also called anemia. Cases of anemia are most often found in teenage girls, due to insufficient nutritional intake, menstruation, and lack of knowledge. The research aims to determine the effect of education about anemia using animation media on knowledge and attitudes. The research was carried out at SMP Negeri 1 Lubuk Pakam in May 2023. The type of research was Quasi-Experimental research with a pretest and posttest design. The population of this study were all class VIII female students with a research sample of 36 female students. The results showed that there were differences in knowledge and attitudes before and after being given counseling about anemia with an average score before counseling of 8.28 and after counseling 13.22. Adolescents' attitudes before counseling were 21.94 and after counseling 33.44. The conclusion of this study found that there was an influence of counseling about anemia using animation media on the knowledge and attitudes of female students at SMP Negeri 1 Lubuk Pakam.